A novel screening framework for waste heat utilization technologies. (15th April 2017) - Oluleye, Gbemi; Jiang, Ning; Smith, Robin; Jobson, Megan
Abstract: Waste heat exploitation improves the energy efficiency of process sites, ensuring lower costs and lower CO2 emissions. Technologies such as organic Rankine cycles, absorption chillers, mechanical heat pumps, absorption heat transformers and absorption heat pumps exist to utilize waste heat. Though these technologies make waste heat re-use technically feasible, selection of technologies based on different heat source temperatures still needs to be addressed. In this work, a novel screening approach is proposed to compare technologies considering the waste heat source quality. A methodology is also presented to select technologies for a process site based on the screening results. Since multiple energy form interactions occur, the screening criterion considers the deviation of the actual performance from the ideal performance of technology options, taking into account irreversibilities as a result of finite temperature heat transfer. The tool is applied to screen and select technologies for waste heat sources below 265 °C. Results identify the temperature ranges where technologies have minimum exergy degradation. The framework systematically matches heat source temperatures with technology options compared to a trial and error approach. The framework was applied to an industrial case study to recover 45, 660 kW of useful energy from the available waste heat. Highlights: Analysis considers deviation from ideal thermodynamic performance of technologies. Five thermodynamic cycles screened for waste heat utilization. Technology choice depends on the heat source temperature. Screening tool presented to visualise results. Screening tool guides technology selection.